Efficient Accommodation Coordination System (EACS) / Maimunah Sulaiman ... [et al.] - Sulaiman, Maimunah; Ahmad, Aishah; A. Jamal, Salamiah; Sumarjan, Norzuwana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
EACS is an efficient coordination system for all Malaysian homestays operated under the consortium origin. It is a system uniquely designed in equality basis that will instantly benefit all the operation business through increased sales and decreased miss management costs. EACS is a combination of the controllable attributes (number of available houses per village, number of available rooms per house and the available capacity per room) and the uncontrollable attributes (number of visitor) that can compute sales of a particular operator and thus indicates the income as a coordinator factor. The novelty EACS include: minimum cost and simple accommodation coordination: user friendly, attractive and effective and recent and unpublished.